Stoleten strukturni razvoj definicij kemijskih terminov, zajetih v slovenskih osnovnošolskih in srednješolskih učbenikih - Sikošek, Darinka (University of Maribor Press, 2019)
Centennial Development of the Semantic Definition of Chemical Concepts (Terms) Included in Primary and Secondary School Textbooks. The monograph presents an overview of the developmental changes in chemical terminology in the field of the Slovenian elementary and secondary school education in the course of the century-old period (1910-2010), with special emphasis on the analysis of textbook definitions of basic chemical terms, selected (sixteen) by the author’s set. The following five terms are covered in the interpretation of analytical results related to the analysis of definitions of these terms from the aspect of their type and structure: Molecule, Chemical Reaction, Compound, Substance (Matter) and Low of Conservation of Mass. The type as a classification criterion is predominantly real (followed by a descriptive and genetic) type of textual definitions of these terms. The complexity of the structure of definitions has been identified; therefore, several synonyms are defined for the same structural element, e.g. of the nearest genus (the genus proximum, g. p.) and consequently also several terms of the species difference (differentia specifica, d.s.). Concerning the textbook - lexical coherence of structural elements of the definitions of these terms, we find their relative consistency, referring to definitions in older textbooks in relation to contemporary lexical definitions.